2013
DOI: 10.1038/mp.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-TrkB signaling through Erk1/2MAPK phosphorylation mediates the enhancement of fear memory induced by glucocorticoids

Abstract: Activation of glucocorticoid receptors (GR) by glucocorticoid hormones (GC) enhances contextual fear memories through the activation of the Erk1/2MAPK signaling pathway. However, the molecular mechanism mediating this effect of GC remains unknown. Here we used complementary molecular and behavioral approaches in mice and rats and in genetically modified mice in which the GR was conditionally deleted (GRNesCre). We identified the tPA-BDNF-TrkB signaling pathway as the upstream molecular effectors of GR-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 92 publications
3
99
0
1
Order By: Relevance
“…Because corticosterone (CORT), the main stress hormone in rodents, was shown to enhance the consolidation of adaptive fear memory in some stressful situations (Phelps, 2004;Quirarte et al, 1997;Revest et al, 2005Revest et al, , 2010Revest et al, , 2014, but also to impair the hippocampal function and disrupt context-based memory in others (Bremner et al, 2004;de Kloet et al, 2005;Sapolsky, 1996), we hypothesized that injections of CORT into the hippocampus, its main brain target, immediately after fear conditioning might either promote adaptive or produce PTSD-like fear memory as a function of the intensity of the stressful event. In order to observe a putative experimental bias toward a cue-based memory at the expense of a hippocampal-dependent context-based memory of the trauma, we used a predicting-context condition in which a discrete (tone) CS is present but irrelevant (not predictive of the US).…”
Section: Hippocampal-amygdalar Interaction Qualify Emotional Memory Rmentioning
confidence: 99%
“…Because corticosterone (CORT), the main stress hormone in rodents, was shown to enhance the consolidation of adaptive fear memory in some stressful situations (Phelps, 2004;Quirarte et al, 1997;Revest et al, 2005Revest et al, , 2010Revest et al, , 2014, but also to impair the hippocampal function and disrupt context-based memory in others (Bremner et al, 2004;de Kloet et al, 2005;Sapolsky, 1996), we hypothesized that injections of CORT into the hippocampus, its main brain target, immediately after fear conditioning might either promote adaptive or produce PTSD-like fear memory as a function of the intensity of the stressful event. In order to observe a putative experimental bias toward a cue-based memory at the expense of a hippocampal-dependent context-based memory of the trauma, we used a predicting-context condition in which a discrete (tone) CS is present but irrelevant (not predictive of the US).…”
Section: Hippocampal-amygdalar Interaction Qualify Emotional Memory Rmentioning
confidence: 99%
“…Enhanced memory formation may involve BDNF-TrkB-MAPK-synapsin Ia/Ib signaling (Revest et al 2005(Revest et al , 2010(Revest et al , 2014 and CaMKII-BDNF-CREB signaling (Chen et al 2012). Yet, it remains to be determined how corticosteroid hormones regulate synaptic function, which is fundamental for memory formation (Rumpel et al 2005;Kessels and Malinow 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies have indicated that BDNF activates MAP kinase and Akt signaling pathways (Chen et al 2013, Revest et al 2014. Therefore, we examined the role of Akt and MAP kinase in HO-1 activation.…”
Section: Bdnf-directed Colon Cancer Cell Migration Involves Vegf Exprmentioning
confidence: 99%